QUANTITATIVE STUDIES OF PHAGOCYTOSIS : Kinetic Effects of Cations and Heat-Labile Opsonin - Stossel, Thomas P. (The Rockefeller University Press, 1973)
Kinetic analysis of the initial ingestion rate of albumin-coated paraffin oil particles by human granulocytes and rabbit alveolar macrophages was undertaken to study the mechanism of action of cations and of heat-labile opsonin on engulfment. The rate of uptake of the particles was stimulated by Ca(++), Mg(++), Mn(++), or Co(++). At high concentrations (> 20 mM) Ca(++) and Mg(++) inhibited the rate of ingestion. Treatment of the particles with fresh serum (heat-labile opsonin) also stimulated the rate of ingestion. (125)I-labeled C3 was bound to the particles during opsonization. C3-deficient human serum lacked opsonic activity, which was restored by addition of purified C3. Normal, C2-deficient, and hereditary angioneurotic edema sera had equivalent opsonic activity. The serum opsonic activity thus involved C3 fixation to the particles by means of the properdin system. Although Mg(++) and heat-labile opsonin both accelerated the maximal rates of ingestion of the particles, neither altered the particle concentrations associated with one-half maximal ingestion rates. Opsonization of the particles markedly diminished the concentrations of divalent cations causing both stimulatory and inhibitory effects on ingestion rates and altered the shapes of the cation activation curves. (45)Ca was not bound to the particles during opsonization. The results are consistent with a mechanism whereby divalent cations and heat-labile opsonin activate ingestion by stimulating the work of engulfment rather than by merely enhancing cell-particle affinity, and whereby heat-labile opsonin acts by potentiating the effects of divalent cations.